Budget Analysis Of Regional Expenditure Of The Environmental Service Of Medan City - Danu Tribowo; Dito Aditia Darma Nasution; Galih Supraja (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
This study aims to analyze the effectiveness of budget utilization at the Medan City Environmental Agency during the 2022–2024 period. The research method used is descriptive quantitative, utilizing secondary data in the form of regional expenditure realization reports. The sample of this study is the budget realization report of the Medan City Environmental Agency during the 2022–2024 period. The analysis was conducted by comparing the stipulated budget and the budget realization each year to assess the effectiveness of budget utilization. The results show that the effectiveness of budget utilization fluctuated during the study period. In 2022, budget realization reached 95% of the total budget and was categorized as effective. However, in 2023 the effectiveness level decreased with realization at 86%, which was included in the fairly effective category. Furthermore, in 2024, budget realization increased to 89%, but remained in the fairly effective category.